Iron deficiency in micro-sized diatoms in the Oyashio region of the Western subarctic Pacific during spring - Hattori-Saito, Ai; Nishioka, Jun; Ono, Tsuneo; McKay, R. Michael L.; Suzuki, Koji (Journal of Oceanography, 2010)
In order to detect iron (Fe) stress in micro-sized (20-200 μm) diatoms in the Oyashio region, western subarctic Pacific during spring, immunological ferredoxin/flavodoxin assays were applied to samples collected from the surface layer in May 2005. Concomitantly, the community composition of the micro-sized phytoplankton and hydrographic conditions, including dissolved Fe and macronutrient concentrations, were also examined. Chlorophyll (Chl) a concentrations were <2 mg m-3 at all sampling stations, except at a station where the Chl a level was 9.0 mg m-3 and a micro-sized diatom bloom occurred. A high abundance of ferredoxin in micro-sized diatoms was detected only at a rather near-shore station where dissolved Fe and macronutrient concentrations were higher, indicating that the micro-sized diatoms did not suffer from iron deficiency. On the other hand, flavodoxin in micro-sized diatoms was often observed at the other stations, including the bloom station, where macronutrients were replete but dissolved Fe concentration was low (0.31 nM). A significant amount of chlorophyllide a, a degradation product of Chl a, was also observed at the bloom station, suggesting a decline of the diatom bloom. The micro-sized phytoplankton species at all the stations were mainly composed of the diatoms Thalassiosira, Chaetoceros, and Fragilariopsis spp. Our study indicates that micro-sized diatoms were stressed by Fe bioavailability during the spring season in the Oyashio region © Springer Science+Business Media B.V. 2010.